ADAB BER -MEDSOS DALAM PERSPEKTIF IBNU ‘ASYUR DAN BUYA HAMKA (KAJIAN ANALISIS TAFSIR QS AL-HUJURAT AYAT 06-08) - Jumroni (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2025)
This study aims to examine the adab of conveying and receiving news in Q.S. Al-Hujurat verses 6-8 according to the perspectives of Ibn 'Asyur and Buya Hamka's interpretations, as well as to analyse its relevance to social media users. This research is a library-based study. The author employs a qualitative descriptive method with a thematic exegesis approach. The findings from both exegetes emphasise the importance of etiquette, tabâyun (verification), which is part of Islamic etiquette, and avoiding evil. These values of goodness need to be applied by social media users, as social media has now become a favourite space for interaction among the general public.